Efficiency of Patient-Controlled Epidural Anesthesia after Lower Limb Joint Replacement Surgery - Gaziev Zoir Tokhirovich1, Kurbonov Erkin Kurbonovich2, Rakhmankulov Eldor Zhurakulovich3, Chakonov U (Institute of Medico-legal Publications Pvt Ltd, 2020)
At present, there are many drugs and method of anesthesia, each has its advantages and disadvantages. Theaim of anesthesia is not only to eliminate suffering and create psychological comfort, but also to improvethe quality of life, accelerate postoperative functional rehabilitation, reduce the incidence of complications.The problem of postoperative pain treatment is relevant both in our country and abroad. According toliterary sources, 30–75% of patients suffer from severe pain in the postoperative period. Today there is agreat number of research, recommendations and guidelines for postoperative anesthesia. (Volchkov V.A.,Kovalev S.V., Kubynin A.N. Modern aspects of postoperative anesthesia (literature review)//Bulletin of St.Petersburg University. Medicine. 2018. V. 13. Issue 3. p. 245-270).